Voice and Culture: A Prospect Theory Approach. (18th September 2014) - Paddock, E. Layne; Ko, Jaewon; Cropanzano, Russell; Bagger, Jessica; El Akremi, Assâad; Camerman, Julie; Greguras, Gary J.; Mladinic, Antonio; Moliner, Carolina; Nam, Kidok; Törnblom, Kjell; Van den Bos, Kees
ABSTRACT The present study examines the congruence of individuals' minimum preferred amounts of voice with the prospect theory value function across nine countries. Accounting for previously ignored minimum preferred amounts of voice and actual voice amounts integral to testing the steepness of gain and loss functions explicated in prospect theory, we use curve fitting to show that ratings of procedural justice fit prospect theory's value function specifically. Further, we investigate the form of this function across nine countries that range in power distance. Results suggest that the form of the value function is congruent with prospect theory, showing an S‐shaped curve that is steeper in the loss than in the gain domain. Further, this pattern is similar across countries. Theoretical and practical implications of these results for both decision making and organizational justice are discussed. Copyright © 2014 John Wiley & Sons, Ltd.